Investigation of particle size distribution of grinded amber by electropulse discharges in a liquid medium - Chornyi, Valentyn; Kharchenko, Yevgen; Mysiura, Taras; Popova, Nataliia; Zavialov, Volodymyr (My University, 2021)
The article presents the study results of electropulse grinding of amber in aqueous and alcoholic media at different amounts of supplied energy. Description of the electropulse grinding laboratory installation, the mechanism of the destruction process of amber particles and methods of statistical processing of experimental data are given. It was established that alcohol medium has a greater impact on the efficiency of crushing than water. Thus, under the same conditions of energy supply, in the aqueous medium the weighted average particle size of amber was 601:6 688:9 m, and in an alcohol medium – 368:0 269:6 m. In an aqueous medium, the particle size decreased to 1/13.6 of raw sample, and in an alcoholic medium to 1/22.3 of raw sample compared to the initial size of raw amber. We found that in the aqueous medium the ratio of large to small fractions is mainly the same with the coefficient of alignment of particles with a size of 1.09. In an alcoholic medium, this ratio significantly differs, with the coefficient of alignment of amber particles of a size of 1.67 with the amount of supplied energy of 125 kJ. В статті представлені результати дослідження електроімпульсного подрібнення бурштину у водному та спиртовому середовищах при різній кількості підведеної енергії. Описано лабораторну електроімпульсну установку, механізм процесу руйнування бурштинових частинок і методів статистичної обробки експериментальних даних. Встановлено, що спиртове середовище має більший вплив на еффективність подрібнення, ніж вода. Таким чином, при однакових умовах підведення енергії, у водному середовищі середньозважений розмір частинок бурштину становив 601 мкм, а в спиртовому середовищі - 368 мкм. У водному середовищі, розмір частинок зменшився до 1/13,6 від необробленого зразка, а в спиртовому середовищі середній розмір частинок зменшився до 1/22,3 в порівнянні із початковим розміром необробленого зразка бурштину. Ми знайшли що у водному середовищі співвідношення крупних та дрібних фракційв основному таке саме, як і коефіцієнта вирівняності частинок за розмірами 1,09. У спиртовому середовищі, це співвідношення суттєво відрізняється, причому коефіциєнт розміру частинок бурштину із розміром 1,67 мкм із кількістю енергії, яку підведено 125 кДж.
Keywords: amber; бурштин; electropulse discharge; електроімпульсний розряд; grinding; подрібнення; particle size distribution; розподіл розмірів частинок; fraction; фракція; кафедра процесів і апаратів харчових виробництв; кафедра технології зберігання і переробки зерна; кафедра експертизи харчових продуктів